The challenge of responding to multiple and compounding food shocks: The case of the Democratic Republic of the Congo - Ulimwengu, John M. (Pontifical Academy of Sciences, 2024)
The Democratic Republic of the Congo (DRC) has been the centre stage of various crises, ranging from political instability, violence and insecurity to the biggest outbreak of Ebola in the world’s history. As a result, the country’s development status remains low, characterised by pronounced malnutrition, high poverty rates and fragile livelihoods (INS, 2019; Marivoet, De Herdt, & Ulimwengu, 2019).